A descriptive method for analysing the Kra Canal decision on maritime business patterns in Malaysia - Noorul Shaiful Fitri Abdul Rahman; Nurul Haqimin Mohd Salleh; Ahmad Fayas Ahmad Najib; Venus Lun (Journal of Shipping and Trade (JST), 2016)
The Kra Canal issue has widely been discussed by maritime players, such as policy makers, regulators, and shipping and port operators. It seems that the idea of developing the Kra Canal is most welcome due to the great savings in costs, higher levels of safety and shortened distance compared to the journey via the Strait of Malacca. This phenomenon will most likely challenge the current maritime business activities in Malaysia because the total foreign going ships that call at the main ports are expected to be reduced. Therefore, the objective of this paper is to study the possible implications of the Kra Canal decision on the changes in maritime business patterns in Malaysia by focussing on the geographical aspects and logistics distribution. A descriptive analysis method will be used together with the PESTLES analysis in addressing the research objective. Finally, the positive and negative implications of the issue discussed are highlighted. Also, future maritime business strategies are proposed after taking into consideration the reshaping of the economies because of the accessibility of this new maritime route.
Keywords: 650; Kra Isthmus canal; Maritime business patterns; Logistics distribution; Port geographic; Maritime economy; PESTLES analysis; Descriptive analysis